2009
DOI: 10.2220/biomedres.30.315
|View full text |Cite
|
Sign up to set email alerts
|

BRAK/CXCL14 expression in oral carcinoma cells completely suppresses tumor cell xenografts in SCID mouse

Abstract: SCID mice are a model of human severe combined immunodeficiency disease and are deficient in B cell function in addition to T cell function. Tumors from other species are easily transplanted into SCID mice and will grow without being rejected. We previously reported that the chemokine BRAK/CXCL14 is expressed in normal cells but its expression is down regulated in an in vitro cancer progression model, suggesting that it has the potential for antitumor activity. Here we report that the growth of BRAK/CXCL14 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 27 publications
(30 reference statements)
0
36
1
Order By: Relevance
“…Cells were lysed with Laemmli buffer consisting of 62.5 mM Tris-HCl (pH 6.8) containing 2% SDS, 8% glycerol, SCC and adenocarcinoma. We reported previously that the forced expression of BRAK/CXCL14 in tongue carcinoma cells decreased the rate of tumor formation and size of tumor xenografts in athymic nude mice (16) and SCID mice (17). In these experiments on cloned cells with an upregulated BRAK/CXCL14 protein expression, the growth of these cells under culture conditions was the same as that of control mock vector-transfected cells.…”
Section: Construction Of Tet-on Brak Vector and Preparation Of Tet-onmentioning
confidence: 64%
“…Cells were lysed with Laemmli buffer consisting of 62.5 mM Tris-HCl (pH 6.8) containing 2% SDS, 8% glycerol, SCC and adenocarcinoma. We reported previously that the forced expression of BRAK/CXCL14 in tongue carcinoma cells decreased the rate of tumor formation and size of tumor xenografts in athymic nude mice (16) and SCID mice (17). In these experiments on cloned cells with an upregulated BRAK/CXCL14 protein expression, the growth of these cells under culture conditions was the same as that of control mock vector-transfected cells.…”
Section: Construction Of Tet-on Brak Vector and Preparation Of Tet-onmentioning
confidence: 64%
“…The functional roles of CXCL14 in tumor biology have been addressed in a number of studies and indicate context-dependent pro-or antitumoral effects (1). Some studies, analyzing effects of CXCL14 overexpression in cancer cells, have reported antitumoral and antiangiogenic effects (3)(4)(5)(6). Protumoral effects of CXCL14 have been suggested based on evidence for upregulation of CXCL14 in the tumor stroma and cancer-associated fibroblasts (CAF; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus in order to investigate whether CXCL14/ BRAK has a tumor-suppressing effect in vivo, we prepared CXCL14/BRAK-expression vector-transfected and mock vector-transfected tongue tumor derived cells and cloned them. The rate of tumor formation in vivo of the former in athymic nude mice or in severe combined immunodeficiency (SCID) mice was significantly lower than that of the latter, even though no difference in the growth rates of these cells was observed under in vitro culture conditions, indicating that CXCL14/BRAK expression in tumor cells suppresses the growth of the cells in vivo (Ozawa et al 2006(Ozawa et al , 2009b.…”
Section: Introductionmentioning
confidence: 99%